Range extension of Kinosternon dunni Schmidt, 1947 (Reptilia, Testudines, Kinosternidae) in Chocó, Colombia - Luis Renteria-Moreno; German Forero-Medina; Mario Garcés-Restrepo; José Rueda-Almonacid (Check List, 2012)
Dunns’ mud turtle Kinosternon dunni is recognized only from a few localities in the drainages of the San Juan, Baudó and Docampadó Rivers in Chocó, Colombia. We report on the occurrence of the species in three new localities in a different drainage, two in the Atrato River drainage, which flows into the Caribbean Sea, and a third locality in the Gulf of Urabá, in the Colombian Caribbean. These new records extend the range of the species approximately 367 km to the north of the closest previous confirmed record.